alright so the question is this:

how do u prove this equation:

log base b times M^k= K times log base b times M

sorry about the writing of the equation, i dunno how to type mathmatically =p

Printable View

- Dec 13th 2005, 07:21 PMabowlofriceprove this log
alright so the question is this:

how do u prove this equation:

log base b times M^k= K times log base b times M

sorry about the writing of the equation, i dunno how to type mathmatically =p - Dec 14th 2005, 12:43 AMCaptainBlackQuote:

Originally Posted by**abowlofrice**

$\displaystyle b^a=M^k$, (definition of $\displaystyle log_b$)

so:

$\displaystyle b^a=(b^{log_b(M)})^k$, (again using the definition of $\displaystyle log_b$).

So:

$\displaystyle a=k.log_b(M)$, (using $\displaystyle (u^v)^w=u^{v.w}$ and $\displaystyle b^a=b^c$ implies $\displaystyle a=c$).

Which is:

$\displaystyle log_b(M^k)=k.log_b(M)$.

RonL - Dec 15th 2005, 09:33 PMabowlofrice
thx man, made me one step closer to loving math.... =]